Temáticas das teses dos programas de pós-graduação em ciência da informação nível seis na capes - Andreia Soares Viana (2016)
The present research is a descriptive-nature study, which used the documental analysis as methodological instrument. One aimed at identifying the themes of the dissertations of the Information Science Post-Graduation Programs (PPGsCI). In order to do so, one selected the PPGsCI which were accredited by the Brazilian Coordination for the Improvement of Higher Education Personnel (CAPES) and received the highest grade in the last evaluation triennium (2010-2012). The results pointed out to the Information Science Post-Graduation Program of the Federal University of Minas Gerais (PPGCI/UFMG) and the Information Science Post-Graduation Program of the São Paulo State University Júlio de Mesquita Filho (PPGCI/UNESP). The universe of this study was composed of 52 theses (30 items of PPGCI/UFMG and 22 items of PPGCI/UNESP). The theses are part of an important scientific collection, since they show the concerns and the problems raised by researchers in a given time period. The analysis of theses, documents which are characteristic of scientific production, may help to understand the tendencies of a field study. Knowing what scientific knowledge is being produced is important as far as it is necessary to know ones own knowledge field in order to plan ones future. The variables analyzed referred to the themes approached in the theses and in their relation to the research lines of the programs. In order to carry out thematic analysis procedures, at first, the dissertations were grouped according to the categories of the Brazilian Thesaurus of Information Science. One opted for this instrument since one considered it wider, more complete and contemporary. This thesaurus is composed of 8 major areas of thematic categories, subdivided in specific topics. Later, one used the Information Science Taxonomy of Donald T. Hawkins in order to classify the theses according to themes. The Taxonomy presents 11 major classes and each one is divided in subtopics. Therefore, this research was based on the assumption that this type of analysis may contribute to Information Science by offering elements to subsidize the planning of post-graduation policies. It was verified that when one used the Thesaurus, the theme category 2 Organization of Knowledge and Information Retrieval presented the highest number of defended theses in the selected period (12 units - 23%), followed by the categories 4 Strategic Information and Knowledge in Organizations and 5 Information and Communication Technologies TICs, with 8 theses each (15%). Therefore, out of a total of 52 theses, 28 units were concentrated in the three categories. Later, with the use of Taxonomy, one confirmed the first result - class 1 Research in Information Science that has as subtopics important matters for Information Science (Research of Information Retrieval; Basic Concepts, Definitions, Theories, Methodologies and Applications; User Behavior and Information Science Usage) presented the highest number of theses, a total of 16 units (31%). It was followed by class 2 Organization of Knowledge, with a total of 11 theses (21%). It is important to point out that the themes identified in the production of theses mostly reflect the characteristics and objectives proposed in the description of research lines of both programs.